Electric field dependences of Curie and Néel phase transition temperatures in magnetoelectric relaxor multiferroic Pb(Fe0.5Ta0.5)O3 crystals seen via acoustic emission. Issue 4 (9th December 2015) - Dul'kin, Evgeniy; Gruszka, Irena; Kania, Antoni; Roth, Michael
Abstract : Pb(Fe0.5 Ta0.5 )O3 magnetic and ferroelectric relaxor multiferroic crystals have been studied under both temperature and dc external electric field conditions by means of acoustic emission technique. All the characteristic relaxor points as Burns T d ≈ 610 K and intermediate T* ≈ 500 K temperatures, as well as both Curie ferroelectric cubic‐tetragonal T c 1 ≈ 259 K and tetragonal–monoclinic T c 2 ≈ 201 K structural and Néel antiferromagnetic–paramagnetic T N ≈ 187 K phase transitions have been successfully detected. It is shown that, when an external dc electric field is applied, both T c 1 and T c 2 exhibit a nonlinear or V‐shape behavior and attain the sharp minima at threshold temperatures T th 1 ≈ 247 K and T th 2 ≈ 200 K with the threshold field E th ≈ 0.1 kV cm −1, as the field enhances, while their acoustic emission count rate monotonically increases. It is shown, too, that the T N behaves linearly in dependence on dc electric field with a negative slope of about −20 K cm kV −1, while its acoustic emission count rate monotonically decreases. All these data are discussed from a viewpoint of presence of polar nanoregions and magnetoelectric coupling effect in Pb(Fe0.5 Ta0.5 )O3 crystals.